Mini cupcakes - Fleming, Lorna (Tunbridge Wells Search Press, 2014)
Mini cupcakes are currently very popular and the enthusiasm for them shows no signs of waning! This book shows readers how to make 20 different themed mini cupcakes, ranging from a basic cupcake covered in buttercream and sprinkles, to mini cupcakes for weddings, Valentine's Day, birthdays and graduation days
2
NEW
Keywords: Cupcakes